Optimization of protocol for chondrocyte isolation from ovine cartilage: Optimization of protocol for chondrocyte isolation from ovine cartilage - Jesslyn, C.M. Nishanthika; Suganya, G; Leela, V; Basha, Sabiha Hayath (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Tissue engineering is one of the most promising alternative therapy for repair of cartilage defects. The large number of cells required for developing cartilage constructs and low cell yield from the cartilage tissue remains the major constraint in cartilage tissue engineering. Hence, an optimised isolation protocol that yields maximum number of viable cells is the first vital step for successful development of cartilage tissue construct. In this study three different isolation protocols using 0.25 % Trypsin-EDTA, 1 % Pronase + 0.4 % Collagenase I and 0.2 % Collagenase II were examined for enzymatic digestion of ovine articular cartilage tissue. Trypan blue staining was used to assess cell yield and viability. Chondrocyte yield per gram was significantly higher (P < 0.05) using collagenase II and exhibited better propagation potential when compared to 0.25 % Trypsin-EDTA and 1% Pronase + 0.4 % Collagenase I. Hence, digestion of ovine cartilage using 0.2% collagenase II yielded highest number of viable cells. Further, the isolated cells expressed chondrocyte phenotype and can be used to produce large number of viable ovine chondrocytes.